NaCl-induced soil stress regulates the diversity of soil bacteria and their ability to metabolize low molecular weight organic acids - Adhari Al-Kalbani; Daniel Menezes-Blackburn; Jinan Waladwadi; Said Al-Ismaily; Buthaina Al-Siyabi (Journal of the Saudi Society of Agricultural Sciences)
Abstract The effects of NaCl-induced soil stress on microbial diversity, enumeration, respiration, and substrate-induced respiration (SIR) induced by low-molecular-weight organic acids were assessed in four Omani date palm farm soils. Eight NaCl doses were used, ranging from no added salt (average EC = 2.1 dS m−1 to a maximum EC of 36.8 dS m−1), generated by adjusting moisture from 5 to 25% (v/v) with saline solutions concentration ranging from 0 to 10% NaCl. All treatments were incubated at room temperature for two weeks before analysis. The carbon sources used in the SIR analysis were glucose and common root exudates (citric, oxalic, succinic, and malic acids) added to 30 µg g−1 of dry soil. Culturable aerobic microbes were quantified using serial dilution (10–2 to 10–4) agar plates on selective media: peptone yeast agar (PYA), glycerol casein agar (GCA), and rose bengal agar (RBA) for bacteria, actinomycetes, and fungi, respectively. Microbial respiration was investigated using the MicroResp™ assay. Soil bacterial and archaeal diversity were assessed using 16S rRNA gene sequencing. Culturable heterotrophic bacterial and actinomycete enumeration showed an 83% decrease at the maximum EC used, whereas fungi decreased by 73%. The addition of NaCl increased the proportion of actinomycetes only at EC values below 10 dS m−1. At the maximum EC, respiration increased by 27%, and the microbial metabolic quotient increased by 631%. In contrast, the SIR was strongly reduced at high EC, indicating that under salt stress, the microbial community was less responsive to external carbon sources like root exudates under salt stress. Moreover, 16S rRNA gene sequence analysis indicated a steep increase in the relative abundance of salt-tolerant bacteria from the phyla Pseudomonadota, Bacillota, and Bacteroidota. This study demonstrated that soil salinity is a strong regulator of soil microbial diversity and function, as reflected by a marked decrease in the responsiveness of soil microbes to various root exudate carbon sources.